Quantity Surveying Firms Survival of Fast Developing Economy - Rahim, F.A.; Abd-Rahman, H.; Wang, C.; Othman, N.D.; Zainon, N. (Journal of Surveying, Construction and Property, 2013)
A recession or an economic downturn gave a tremendous impact on the Malaysian construction industry. The financial crisis seemed to be a wake-up call to all of the practitioners in the construction industry. Many of the QS consultant firms took strategic approaches to overcome the strike of the recession or economic downturn. The objective of this research is to determine the reaction of QS consultant firms towards the crisis that struck the nation Malaysia, a fast developing economy. Besides, this research reveals the recipe of survival of various QS consultant firms from the turmoil. Towards the end, the paper suggests suitable approaches to mitigate the impacts from an economic downturn for future survival of QS consultant firms. Data were collected through a questionnaire survey. The impact of an economic downturn or recession on QS consultant firms are seen in the decline of jobs, projects, and professional fees. Management theories were the main weapon used by the QS consultant firms to mitigate the negative impacts.